Neutrophils increase or reduce parasite burden in Trypanosoma cruzi-infected macrophages, depending on host strain: role of neutrophil elastase. - Tatiana Luna-Gomes; Alessandra A Filardy; Juliana Dutra B Rocha; Debora Decote-Ricardo; Isabel Ferreira LaRocque-de-Freitas; Alexandre Morrot; Patrícia T Bozza; Hugo C Castro-Faria-Neto; George A DosReis; Marise P Nunes; Célio G Freire-de-Lima (PLoS ONE, 2014)
Neutrophils are involved in the initial steps of most responses to pathogens and are essential components of the innate immune response. Due to the ability to produce and release various soluble mediators, neutrophils may participate in the regulation of the inflammatory response. Little is known about the role of neutrophils during protozoan infections including infection by Trypanosoma cruzi. In the present study we investigated the importance of inflammatory neutrophils on macrophage activation and T. cruzi replication in vitro, in cells obtained from BALB/c mice and C57Bl/6 mice. Co-cultures of BALB/c apoptotic or live neutrophils with infected peritoneal macrophages resulted in increased replication of the parasites and in the production of TGF-β and PGE2. The treatment with anti-TGF-β neutralizing antibody and COX inhibitor blocked the parasite replication in vitro. On the other hand, co-cultures of T. cruzi infected macrophages with live neutrophils isolated from C57BL/6 mice resulted in decreased number of trypomastigotes in culture and increased production of TNF-α and NO. The addition of anti-TNF-α neutralizing antibody or elastase inhibitor resulted in the abolishment of macrophage microbicidal effect and increased parasite replication. Addition of elastase to infected macrophages reduced the replication of the parasites, and on the other hand, addition of a selective inhibitor of iNOS increased parasite growth, suggesting the role of NO in this system. Our findings reveal that neutrophils may regulate T. cruzi experimental infection and determine susceptibility and resistance to infection.